2016
DOI: 10.3389/fpsyg.2016.01388
|View full text |Cite
|
Sign up to set email alerts
|

Does Loneliness Necessarily Lead to a Decrease in Prosocial Behavior? The Roles of Gender and Situation

Abstract: Although, previous studies show overwhelming evidence that loneliness is negatively correlated with prosocial behavior, some theories and research have implied that under certain situations, loneliness plays a positive role in an individual's social functioning. The two studies reported in this article examined loneliness and its associations with prosocial behavior in Chinese adults using subjective reporting and experimental design. Study 1 examined 305 Chinese adults (175 males) using the Social and Emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…Male LBAs scored significantly lower on pro-social tendency than did females. Accumulating researches have demonstrated that males and females exhibit different methods of mental processing (Haferkamp et al, 2012; Gohier et al, 2013) and have found gender differences in social functioning (Huang et al, 2016). Seemingly, an unacceptable social environment could elicit opposite behaviors from females and males.…”
Section: Discussionmentioning
confidence: 99%
“…Male LBAs scored significantly lower on pro-social tendency than did females. Accumulating researches have demonstrated that males and females exhibit different methods of mental processing (Haferkamp et al, 2012; Gohier et al, 2013) and have found gender differences in social functioning (Huang et al, 2016). Seemingly, an unacceptable social environment could elicit opposite behaviors from females and males.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness and social isolation is also a risk factor for mortality (Holt-Lunstad et al, 2015;Rico-Uribe et al, 2016) and is related with physical illnesses, such as diabetes, autoimmune disorders, cardiovascular diseases, cancer, and many others (Mushtaq et al, 2014). Loneliness is also negatively related to prosocial tendencies (Huang et al, 2016) and influences the mental and physical quality of life (Gerino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cloninger et al 19 found that the effect of work family conflict on OCBs was stronger for females than males. Similarly, Huang et al 23 revealed a stronger negative effect of loneliness on prosocial behavior for females than males. Considering that women are more vulnerable to the impacts of poor relationships, 19,23 we argue that the effects of workplace loneliness on OCB via work engagement may be stronger for women than men.…”
Section: Introductionmentioning
confidence: 89%